Optimisation of retention of Mangiferin in Cyclopia Subternata during preparation for drying and storage of green honeybush and development of Nir Spectroscopy Calibration models for rapid quantification of Mangiferin and Xanthone contents - Maicu, Maria Christina (Stellenbosch : Stellenbosch University, 2008)
Thesis (Msc Food Sc (Food Science))--Stellenbosch University, 2008.